Benefits of Building Information Modelling in the Project Lifecycle: Construction Projects in Asia. (22nd August 2014) - Li, Jian; Wang, Ying; Wang, Xiangyu; Luo, Hanbin; Kang, Shih-Chung; Wang, Jun; Guo, Jun; Jiao, Yi
Building Information Modelling (BIM) is a process involving the creation and management of objective data with property, unique identity and relationship. In the Architecture, Engineering and Construction (AEC) industry, BIM is adopted a lot in the lifecycle of buildings because of the high integration of information that it enables. Four-dimensional (4D) computer-aided design (CAD) has been adopted for many years to improve the construction planning process. BIM is adopted throughout buildings' lifecycles, in design, construction and operation. This paper presents five large-scale public and financial projects that adopt BIM in the design, construction and operational phases. Different uses of BIM are compared and contrasted in the context of the separate backgrounds. It is concluded that productivity is improved where BIM is used to enable easy sharing and integration of information and convenient collaboration.